Research and Assessment of Asphalt Layers Bonding - Audrius Vaitkus; Daiva Žilionienė; Sabina Paulauskaitė; Faustina Tuminienė; Laura Žiliūtė (The Baltic Journal of Road and Bridge Engineering, 2011)
The bonding of asphalt layers has direct reliance on road pavement structures strength and durability. Because of insufficient bond between pavement layers the slippage and corrugations, rutting and cracking occur and the pavement life cycle becomes shorter. The article describes the research on bonding of asphalt layers, which was carried out in 2010–2011 at Vilnius Gediminas Technical University Road Research Institute. In this research the strength of layers bonding was assessed using the direct shear (Leutner) test without normal stress in the specimen. The samples were taken from the road sections of Lithuania with standard asphalt layers, also asphalt layers with the geosynthetic interlayer. The research showed that the bonding strength of asphalt layers of the samples taken on the roads of Lithuania in most cases meets the requirements of standard documents, and the use of geosynthetic materials between asphalt layers worsens their bonding strength.